19F NMR Spectroscopy as a Probe of Cytoplasmic Viscosity and Weak Protein Interactions in Living Cells. Issue 38 (6th August 2013) - Ye, Yansheng; Liu, Xiaoli; Zhang, Zeting; Wu, Qiong; Jiang, Bin; Jiang, Ling; Zhang, Xu; Liu, Maili; Pielak, Gary J.; Li, Conggang
Abstract Protein mobility in living cells is vital for cell function. Both cytosolic viscosity and weak protein–protein interactions affect mobility, but examining viscosity and weak interaction effects is challenging. Herein, we demonstrate the use of 19F NMR spectroscopy to measure cytoplasmic viscosity and to characterize nonspecific protein–protein interactions in living Escherichia coli cells. The origins of resonance broadening in Escherichia coli cells were also investigated. We found that sample inhomogeneity has a negligible effect on resonance broadening, the cytoplasmic viscosity is only about 2–3 times that of water, and ubiquitous transient weak protein–protein interactions in the cytosol play a significant role in governing the detection of proteins by using in‐cell NMR spectroscopy.